Total Polyphenols, Flavonoids Contents and Antioxidant Activity of Crude Methanolic and Aqueous Extracts for Some Medicinal Plant Flowers - Erian, N.S; Hamed, H. B.; El-Khateeb, A. Y. (Arab Journal for Sciences and Research Publishing, 2016)
The total polyphenols and flavonoids contents of C. cardunculus, A. millefolium, C. officinalis, and M. chamomilla flowers, C. officinalis flowers have the highest of total polyphenols and flavonoids contents, which were 86.11 mg GAE/g and 11.59 mg GAE/g, respectively. Methanolic and aqueous extracts of plant flowers was antioxidant activity by used (FRAP, ABTS and DPPH) The methanolic and aqueous extracts of C. officinalis flowers have the highest reducing power which was ranged from 0.5054 to 1.8019 and 0.4215 to 1.3153 at the concentrations of 10 and 80 mg/ml, respectively. Also, by used (ABTS) it could be  percentage  were 90.17and 79.31%,  While, by used (DPPH) it could be  percentage of inhibition (IC50) which were 0.004 and 0.006 for methanolic and aqueous extracts respectively.
Keywords: polyphenols; flavonoids; plant extracts; antioxidant activity; (FRAP-ABTS-DPPH)